Methylation of the hippo signalling effector YAP by SETD7 drives myocardial ischemic injury. (25th November 2020) - Ambrosini, S; Montecucco, F; Akhmedov, A; Mohammed, S.A; Brown, P; Rossi, F; Kiss, A; Luscher, T.F; Costantino, S; Paneni, F
Abstract: Introduction: Myocardial ischemia/reperfusion (I/R) injury is one of the most deleterious cardiovascular conditions and a leading cause of mortality. The Hippo pathway effector YAP critically regulates cardiomyocyte proliferation and survival during myocardial I/R injury. However, the mechanisms regulating YAP activation in this setting remain poorly understood. Post-translational modifications of proteins, namely methylation, modulate pathways implicated in myocardial I/R injury. The methyltransferase SETD7 is emerging as a regulator of cell survival via methylation of histone and non-histone proteins. Whether SETD7 participates to myocardial I/R injury remains elusive. Purpose: To investigate the role of SETD7 in regulating Hippo signaling during myocardial I/R injury. Methods: Neonatal rat ventricular myocytes (NRVM) were exposed to normal glucose levels or glucose deprivation (GD) for 15 h, in the presence of the selective SETD7 inhibitor [(R)-PFI-2] or its inactive enantiomer [(S)-PFI-2]. Western blot and real time PCR were employed to investigate the effects of energy stress on SETD7 and the Hippo pathway, while apoptosis was assessed by Caspase-3 activity assay. YAP activity was assessed through chromatin immunoprecipitation assay (ChIP), its localization was examined by confocal microscopy while mono-methylation was assessed by immunoblotting. SETD7 knockout (SETD7−/−) mice and wild-type (WT) littermates (male, 8–12 weeks old) underwent 1 h of left anterior descending (LAD) coronary artery ligation followed by 24 h of reperfusion. Infarct size was assessed by TTC staining and shown as infarct size per ventricle surface (I/V). Cardiac function was investigated at 24h by conventional and Tissue Doppler Imaging (TDI) echocardiography. Results: GD in NRVMs led to upregulation of SETD7 and physical interaction with the pro-survival transcriptional cofactor YAP, resulting in its direct mono-methylation. Furthermore SETD7-dependent methylation of YAP led to its cytosolic retention and subsequent reduction of YAP binding to the promoter of pro-survival genes. Of note, pharmacological inhibition of SETD7 by (R)-PFI-2 blunted YAP mono-methylation while restoring its nuclear retention. Mechanistically, SETD7 inhibition promoted YAP binding to catalase and superoxide dismutase (SOD) gene promoters, thus preventing GD-induced mitochondrial oxidative stress and apoptosis. In line with our in vitro findings, SETD7−/− mice showed decreased infarct size as compared to WT littermates and preserved cardiac systolic (ejection fraction, fractional shortening) and diastolic function, as assessed by both conventional and TDI echocardiography. Conclusions: We show that SETD7-dependent methylation of YAP is required for its inactivation, thus leading to myocyte oxidative stress and apoptosis. Pharmacological modulation of SETD7 by (R)-PFI-2 may represent a new therapeutic approach to prevent myocardial ischemic damage through modulation of the Hippo pathway. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss Heart Foundation